(untitled) (Contemporary Journal of Social Science Review, 2025)
Electoral integrity is widely regarded as the cornerstone of democratic legitimacy, yet in many hybrid political systems it remains contested, negotiated, and unevenly practiced. This article critically re-examines electoral integrity in Pakistan by situating elections within the broader tension between citizen choice and institutional control. Drawing on a qualitative analysis of electoral laws, institutional practices, media narratives, and post-election controversies, supplemented by secondary data from election reports and scholarly literature, the study interrogates how formal democratic procedures coexist with informal power structures. The article argues that while Pakistan’s electoral framework constitutionally guarantees universal suffrage, political competition, and procedural transparency, the realization of these principles is frequently constrained by structural interventions, elite dominance, and uneven enforcement of electoral regulations. Particular attention is given to the role of the Election Commission of Pakistan, the judiciary, political parties, and media actors in shaping both the conduct and perception of elections. The findings suggest that electoral integrity in Pakistan is not simply undermined by isolated irregularities but is systematically influenced by power asymmetries that blur the boundary between democratic choice and political management. Elections thus function simultaneously as mechanisms of participation and as instruments of legitimacy for entrenched authority. By conceptualizing elections as arenas of negotiated democracy rather than purely procedural events, this study contributes to broader debates on electoral governance in transitional and hybrid regimes. The article concludes by highlighting the need for institutional reforms, normative consensus on civilian supremacy, and strengthened accountability mechanisms to move Pakistan’s electoral system closer to substantive democratic integrity rather than symbolic compliance.